2 Out of Hour and Weekend Admission to Hospital with Acute Coronary Syndrome Confers Poorer Mortality and Longer Length of Hospital Stay. (6th June 2015) - Potluri, Rahul; Chandran, Suresh; Uppal, Hardeep
Abstract : Introduction: Acute Coronary Syndrome (ACS) is the most common cardiovascular diagnosis requiring hospital admission worldwide and in the UK. ACS comprises of a spectrum including ST segment elevation Myocardial Infarction (MI), Non-ST segment elevation MI and Unstable Angina. It is associated with substantial mortality and healthcare burden. Given the current five day working pattern in the UK, we hypothesise a significant variation in the outcomes of patients admitted with ACS during the standard working hours compared with out of hours and weekends. SCAD is symptomatic and easier to tackle compared with asymptomatic patients. Methods: Anonymous data of adult patients aged ≥ 18 with all types of ACS admitted to 7 hospitals between 2000 and 2013 was obtained and processed using the ACALM (Algorithm for Co-morbidity, Associations, Length of stay and Mortality) study protocol. ACALM uses the ICD-10 and OPCS-4 coding systems to identify patients and the methodology has been used and published widely. Analyses were performed comparing mortality and length of hospital stay between admissions according to the day of the weeks and core working hours (0900 to 1700 Monday to Friday) and out of these hours. Results: Of 929465 adult patient population there were 25294 patients with ACS. Mean age 67 years; Male 64.2%. Over the study period, 38.2% of the patients died after ACS during their follow-up period. However, patients admitted on Saturday or Sunday had significantly higher values of 43.3% and 39.9% respectively. Patients admitted outside of the normal working hours had a value of 39.1% compared with 36.5% for patients admitted during working hours. The mean length of hospital stay (LOS) was significantly higher for patient admitted on Saturday and Sunday and outside of core working hours (p < 0.05). Table 1 shows these results in full. Conclusion: Day and time of hospital admission confer significant variations in outcomes such as mortality and LOS in patient with ACS. These disparities further fuel the argument for 24/7 specialist care in the UK.